2022
DOI: 10.1002/nop2.1194
|View full text |Cite
|
Sign up to set email alerts
|

Current occupational well‐being status and protective and risk factors of male nurses in Chengdu, China: A cross‐sectional study

Abstract: Aims: This study explores the current occupational well-being status of male nurses in Chengdu, China, and identifies the concomitant protective and risk factors. Design:This study has a cross-sectional survey design.Methods: From 13 July to 21 July 2019, a cross-sectional survey involving 209 male nurses in 7 tertiary hospitals in Chengdu, China, was conducted using a general information questionnaire, the Mindfulness Attention Awareness Scale, the Acceptance and Action Questionnaire-II, the Professional Iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…For male students at junior colleges, focusing on practical skills will allow them to obtain higher levels of professional achievement (Feng et al, 2016 ), while training for students at undergraduate and key undergraduate schools should be more diverse, reflecting the individualized teaching mode used in the real world. Teachers should not only have rich clinical experience and solid theoretical knowledge, but should also provide positive psychological guidance in response to the students' mental and emotional changes (Aydın et al, 2021 ; Waddell et al, 2015 ; Wang et al, 2022 ) to help them transition into the nursing industry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For male students at junior colleges, focusing on practical skills will allow them to obtain higher levels of professional achievement (Feng et al, 2016 ), while training for students at undergraduate and key undergraduate schools should be more diverse, reflecting the individualized teaching mode used in the real world. Teachers should not only have rich clinical experience and solid theoretical knowledge, but should also provide positive psychological guidance in response to the students' mental and emotional changes (Aydın et al, 2021 ; Waddell et al, 2015 ; Wang et al, 2022 ) to help them transition into the nursing industry.…”
Section: Discussionmentioning
confidence: 99%
“…In China, a developing country, this proportion is less than 1% (Feng et al, 2016 ). Although the proportion of male nurses has increased in recent years, the rate of growth is very slow (Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a positive psychological feeling that guides the pursuit of good, well‐being has a lasting impact on all aspects of people and, as an indicator of the overall assessment of an individual's quality life, it has an extremely important place in all walks of life. In particular, the nursing profession, with its heavy workload and complex environment, puts a heavy physical and mental pressure on clinical nurses, which affects their well‐being and quality of care (Javanmardnejad et al, 2021; Wang et al, 2022). Nurses' well‐being refers to a series of positive experiences in work and life, reflecting their happiness index in working life, and the well‐being of nurses is not only related to their own health, but also affects their work status and behaviour, which in turn has an impact on the quality of clinical care (Patrician et al, 2022; Xiao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Chinese male nursing students’ self-esteem and professional identity are positively correlated ( Cao et al, 2016 ). The professional identity of male nursing students and male nurses is subject to constant change, and affirming the importance and value of male nurses themselves can help to increase self-esteem and thus enhance professional identity ( Zhang, 2019 ). There are far fewer male nursing students and male nurses in China than their female counterparts, and they are more willing to leave the profession ( Tong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%